Screening in silico Alkaloid Compounds Inhibiting Estrogen-α Receptors Against Breast Cancer - Phuc Loc, Bui; Manh Hung, Vu; Thi Thuy, Nguyen; Hoang Mai, Tran; Thi Huong, Le; Thi Hong Ngoc, Tran; Thi Hong Khanh, Do; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3, 2022)
Abstract: The estrogen-α (ER-α) receptor is an important target in breast cancer therapy. Alkaloids are a class of plant extracts that have the potential to inhibit ER-α receptors. In this study, we evaluated the ability of alkaloids to inhibit ER-α receptors by molecular docking method. Based on previous publications, we collected 52 alkaloid compounds. The results showed that there were 4 compounds with stronger inhibitory effects on ER-α receptors than positive controls, which are co-crystallized ligands with 4-hydroxytamoxifen. Conducting analysis according to Lipinski's 5-criteria rule and predicting pharmacokinetic-toxicological parameters, we obtained one compound with drug-like properties is Pityriacitrin B. Therefore, this compound has the potential to develop into drugs that inhibit ER-α receptors for breast cancer treatment. Keywords: Breast cancer, ER-α, molecular docking, alkaloid, Pityriacitrin B.